2021
DOI: 10.1186/s13011-021-00386-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between family intimacy and relapse tendency among people who use drugs: a moderated mediation model

Abstract: Background Drug addiction is difficult to overcome. The relapse rate is high, and the negative impact on individuals, families and society is severe, therefore exploring social psychological mechanisms to reduce relapse has very important theoretical and practical value. However, the underlying mechanism by which the interaction between family and individual factors influences the tendency to relapse remain unclear. Thus, the purpose of this paper is to discuss the relationship between family i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…Communication is associated with parent-child relationship and family functioning [ 73 ]. Problematic family relationships are a risk factor for the development of PG [ 74 ] and relapse of addictive disorders [ 75 ]. They were indirectly addressed in modules 2 and 3 by externalizing the child’s problematic behavior as well as supporting positive views on the child and joint time.…”
Section: Discussionmentioning
confidence: 99%
“…Communication is associated with parent-child relationship and family functioning [ 73 ]. Problematic family relationships are a risk factor for the development of PG [ 74 ] and relapse of addictive disorders [ 75 ]. They were indirectly addressed in modules 2 and 3 by externalizing the child’s problematic behavior as well as supporting positive views on the child and joint time.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies of substance users in Taiwan have the same findings, i.e., that there was no simple and objective standard for whether family factors have an adequate protection effect for substance users [ 75 ], whether or not substance users themselves have good psychological adjustment ability [ 76 ], and that how to understand and interpret family environment factors [ 77 ] was the key. The latest studies also found that psychological capital played a mediating role between family closeness and relapse tendency [ 78 ], and life strategies could also regulate the mediating effect of psychological capital [ 79 ]. In conclusion, the family can only provide limited assistance, and the important factor that really determines whether substance user to “quit drugs” or not is still the individual’s psychological state and the significance given to family factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A social support network is a crucial element in the life of people who use drugs (PWUD) because isolation and loneliness have an overwhelming effect on drug addiction. So that the consequence of social distancing measures during the pandemic puts the efforts of recovery at risk (Zeng et al , 2021). Moreover, the sense of belonging and the length of time in treatment is a crucial component in the recovery process.…”
Section: Social Support Networkmentioning
confidence: 99%